The Demon Headmaster and the Prime Minister's brain - Cross, Gillian (Oxford : Oxford University Press, 2017)
There's a new computer game at school and the chance to enter the Junior Computer Brain of the Year competition is sending ripples of excitement through the pupils. Dinah is a whizz at the game and soon finds herself in the competition final. But it takes a while to realize that it's all just part of the Demon Headmaster's latest plan . . . Dinah is being used to access the computer of the Prime Minster. Great fun and just a little bit frightening, Gillian Cross's Demon Headmaster books still hold readers under their hypnotic spell. Fast-paced and full of adventure, they're impossible to resist!
Originally published: as The Prime Minister's brain. 1985.
Keywords: Demon Headmaster -- (Fictitious character) -- Juvenile fiction; Children's stories